Evolution of Juvenile Ankylosing Spondylitis - Ye.V. Prohorov; I.V. Tov; A.Yu. Yakovlenko; O.V. Sinyachenko; L.N. Antonova (Zaslavsky O.Yu., 2012)
More frequent involvement of elbow and ankle joints, development of enthesopathies, changes in intraarticular meniscal horns, forming of Baker's cyst, cartilage flaps and systemic osteoporosis are peculiar to juvenile ankylosing spondylitis evolution, and the sum of significance of these signs exceeds 13 times the same in patients with onset in adult stage, but the spine injury is less peculiar to juvenile ankylosing spondylitis. Age dimorphism of results of several drug groups and physiotherapeutic measures is observed.